Properties of Al doped CdZnTe film by aluminium induced crystallisation. (3rd March 2016) - Zeng, D.; Mu, Y.; Meng, J.; Liu, W.; Chen, F.; Zhou, H.
Abstract : Al doped CdZnTe film was prepared by radio frequency magnetron sputtering with aluminium induced crystallisation. Structural and electric properties of Al doped CdZnTe film were studied. Al doped CdZnTe film has a preferred [111] orientation with uniform pebble-like grain structure, and the leakage current is 2·3 × 10 − 8 A. Current conduction mechanism in Al doped CdZnTe film has been investigated and analysed. Space charge limited current emission is found to be the dominant mechanism in Al doped CdZnTe film, which was associated with trapping process of Cd vacancies.